PENGARUH SUBSTITUSI RUMPUT GAJAH DENGAN PELEPAH DAUN SAWIT TERHADAP KECERNAAN BAHAN KERING DAN ORGANIK, SERTA HUBUNGAN ANTARA KEDUA KECERNAAN PADA KAMBING - Dewi Fatimah Yusuf; Farida Fathul; Liman . (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The research aimed to determine the effect of substitution between elephant grass with leaves midrib palm oil on dry matter intake, production of feces, digestibility of dry matter and organic; determine the effect of substitution of elephant gras and leaves midrib palm oil; and determine the relationship between digestibility of dry matter and orgnanic on goats.The research uses a randomized block design (RBD), with an average weight of goats 9-21 kg/headconsisting of three treatments with three replications ie R1 = 80% concentrate + 20% elephant grass, R2 = 80% concentrate + 20% leaves midrib of palm oil without fermentation, and R3 = 80% 5 concentrate + 20% fermented leaves midrib palm oil.  The research was on October – November 2015, at the home Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The data obtained were analyzed using analysis of variance (ANOVA) on the real level of 5% or 1%.  If the treatment shows the real effect, then do a further test Duncan at 5% or 1%. Regression to determine the relationship between dry matter digestibility and organic matter digestibility at the level of 5% or 1%.The results showed substitution elephant grass with leaves midrib palm oil not significant (p>0.05) on feed consumption, but significant (p <0.05) on the production of feces and highly significant (p <0.01) the digestibility dry matter and organic.The relationship between the dry matter and organic by the equation  Ŷ = - 3.629 + 1,0249x, coefficient of determination (R2) 99.77%, and the value of the correlation (r) +0.9969. (Keywords: goat, leaves midribpalm oil, feed consumption, production of feces, digestibility of dry matter and organic)